Duality and Fallibility in Practices of the Self: The ‘inclusive subject’ in diversity training - Brewis, Deborah N. (Organization studies, 2019)
The concept of ‘inclusion’ has been gaining ground in a field known as equality and diversity work. Scholars have begun to both theorise what this concept means as a normative goal and to critically examine how it is mobilised in organisational practice. This paper contributes to the latter conversation by asking what comes to count as ‘doing inclusion’ at the level of the individual. I examine the practices of diversity training in United Kingdom organisations, in which diversity practitioners seek to transform their trainees into people who will act inclusively toward others, asking: Who is the ‘inclusive subject’ that is being constructed – imagined, sought and legitimised – through diversity training? What are the conditions of possibility that shape the emergence of this subject? And what are the possibilities that this subject affords to marginalised groups struggling for recognition within organisations? The analysis mobilises Foucault’s notions of power/knowledge, discipline, and practices of the self to describe and discuss the performance of inclusive subjectivity in the context of diversity training in the UK. The practices described are found to be facilitated by two key forms of knowledge about how the subject is characterised: duality and fallibility. The discussion of these two forms of knowledge leads us to consider the relations of both discipline and freedom that take place in diversity training.